The effect of circulating progesterone on magnitude of the GnRH-induced LH surge: Are there any differences between Bos indicus and Bos taurus heifers? - Batista, E. O.S.; Del Valle, T. A.; Ortolan, M. D.D.V.; Rennó, F. P.; Nogueira, G. P. [UNESP]; Souza, A. H.; Baruselli, P. S. (Elsevier, 2017)
This study evaluated the effects of differing circulating progesterone (P4) levels on the luteinizing hormone (LH) surge profile following treatment with gonadotropin releasing hormone (GnRH) in B. indicus (Nelore, n = 13) and B. taurus (Holstein, n = 16) heifers. All heifers were synchronized with a hormonal protocol to induce either a Low or High circulating P4 environment at the time of GnRH treatment. Heifers were randomly assigned to a 2 × 2 factorial design composed by two genetic groups (B. indicus and B. taurus) and two levels of circulating P4 concentrations (Low or High). Blood samples were collected every 30 min from −30 to 210 min and at 270 min after GnRH treatment. As expected, mean P4 concentration was greater for cows in the High than in the Low P4 group (P = 0.0008) and in Bos indicus than in Bos taurus heifers (P = 0.06). Despite genetic group, the area under the curve of LH release was greater in the Low-P4 than in High-P4 concentration group (P < 0.0001). Interestingly, it appears that High P4 concentrations had a more pronounced effect on LH peak in B. indicus than in B. taurus heifers, as indicated by the interaction (P = 0.01) between genetic group and P4 levels. In conclusion, circulating P4 concentration have a great impact on the GnRH-induced LH surge of both B. indicus and B. taurus heifers, but it does not explain the much lower LH peak in B. indicus with low circulating P4. Thus, more studies are essential to uncover some of the underlying physiological factors other than circulating P4 that are limiting LH release following a GnRH treatment in B. indicus cattle.
Keywords: Circulating P4; GnRH; Holstein; LH; Nelore